2020
DOI: 10.21873/anticanres.14003
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin-regulated MicroRNA-301-3p Targets Caspase-8 and Modulates TRAIL Sensitivity in PANC-1 Cells

Abstract: Background/Aim: MicroRNAs (miRNAs) play regulatory roles in pancreatic ductal adenocarcinoma (PDAC). However, it is still required to identify the function of miRNA-301-3p in pancreatic cancer cells. Materials and Methods: Effects of luteolin on cell growth, TRAIL cytotoxicity, and miR-301-3p levels were evaluated. The role of miRNA-301-3p in regulating cell proliferation, target gene expression, and TRAIL cytotoxicity were studied. Results: The levels of miR-301-3p were down-regulated in PANC-1 cells exposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…This reduced migration and invasion of A431-III cells and decreased metastasis in a xenograft zebrafish model [384]. Similarly, miRNA-301-3p was downregulated in pancreatic cancer cells following treatment with luteolin, causing a decrease in cell growth [380]. In several ovarian cancer cell lines, luteolin induced apoptosis through the extrinsic and intrinsic pathways.…”
Section: Luteolinmentioning
confidence: 92%
See 1 more Smart Citation
“…This reduced migration and invasion of A431-III cells and decreased metastasis in a xenograft zebrafish model [384]. Similarly, miRNA-301-3p was downregulated in pancreatic cancer cells following treatment with luteolin, causing a decrease in cell growth [380]. In several ovarian cancer cell lines, luteolin induced apoptosis through the extrinsic and intrinsic pathways.…”
Section: Luteolinmentioning
confidence: 92%
“…Caused cell cycle arrest [362,[374][375][376][377]. Decreased cell viability and proliferation [378][379][380][381][382][383].…”
Section: Luteolinmentioning
confidence: 99%
“…Antrocin [119], benzyl isothiocyanate [120], capsaicin [121], curcumin [122], quercetin [123], genistein [124], ginsenoside [125], emodin [126], oleuropein [127], resveratrol [128], and other secondary metabolites that could affect the regulation of miRNAs' expression and their natural sources are shown in Table 1. Evidence-Based Complementary and Alternative Medicine Achillea millefolium (Asteraceae) [143] Evidence-Based Complementary and Alternative Medicine [154]. Also, Wang et al reported that the therapeutic potential of fish oil supplementation on cholesterol metabolic disorder and hepatic triglyceride is mediated through regulating the particular miRNAs' expression (rno-miR-33-5p and rno-miR-34a-5p) in Westernstyle diet-induced NAFLD rats [155].…”
Section: Modulation Of Mirna Levels By Natural Productsmentioning
confidence: 99%
“…In pancreatic cancer cells, luteolin treatment is associated with down-regulation of miR-301-3p, which directly targets caspase-8, an initiator of the extrinsic apoptosis pathway. Also, luteolin treatment and knockdown of miR-301-3p sensitized pancreatic cancer cells to the tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL) ( Moeng et al, 2020 ). This is a potent apoptosis inducer of the TNF cytokine superfamily, which was also tested as a recombinant anti-cancer agent, but with reported high resistance rates after repeated treatments ( Wong et al, 2019 ).…”
Section: Phenolic Compoundsmentioning
confidence: 99%